Case report: Localized xanthogranulomatous pyelonephritis in children: A case report and literature review - Deng, Qi-Fei; Chu, Han; Peng, Bo; Liu, Xiang; Cao, Yong-Sheng (Frontiers in Pediatrics, 2022)
Background: Xanthogranulomatous pyelonephritis (XGPN), which is featured by inflammatory destruction of renal parenchyma and fibrosis of kidney, occurs mainly among adults, sporadically among children and rarely among infants. Recurrent urinary tract infections, kidney stone-induced obstructive nephropathy, malnutrition, abnormal lipid metabolism, hypoimmunity, lymphatic obstruction and congenital urinary abnormalities may all cause XGPN among children. Its primary treatment is radical nephrectomy. Case description: In this study, we describe a rare case of XGPN in a 7-year-old boy infected with Staphylococcus aureus (S. aureus). The child presented with symptoms including recurrent fever, urine culture negative. The postoperative pathology confirmed XGPN. Besides, partial nephrectomy was performed. Conclusion: XGPN, as a special type of chronic pyelonephritis, is a rare pyelonephritis requiring surgical treatment. Early diagnosis and treatment are crucial to reducing its morbidity and mortality. Although radical nephrectomy is the primary therapeutic option for patients with XGPN, partial nephrectomy surgery should be considered for focal XGPN, aiming to preserve residual renal function in children as far as possible.